Indigenous Knowledge Systems and Rangeland Governance in Northern Tanzania - Kisiaya, Saruni (Tanzania Journal for Population studies and Development, 2016)
The article examines the role of indigenous knowledge (IK) systems in the governance of common-property rangeland resources among pastoral communities in Northern Tanzania. It draws on the political ecology approach to examine the role and state of indigenous knowledge on rangeland governance in the changing socio-cultural, political and ecological context. It employs qualitative methodology to capture the narratives from the indigenous people. Using purposive (non-probability strategy) technique, the study obtained a sample of 50 interviews and life histories combined, and four focus group discussions from four research sites. Findings indicate that forms of indigenous knowledge—such as rangeland rituals and cosmologies, rangeland zonation, livestock taxonomy, water communism and pastoral mobility—regulate and maintain a harmonious relationship between indigenous people and the wider ecosystem. The article concludes that IK should be recognized as an integral component of local resource governance. Also, indigenous rangeland cooperatives should be formed to help the sustainability of IK systems and settling emerging rangeland disputes.